Kharābāt : Dar bayān-i ḥikmat, shajāʿat, iffat u ʿadālat bih payrawī az Gulistān-i Saʿdī - Shīrāzī, Faqīr (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Persianate world, wisdom literature has a long history, dating back to pre-Islamic times. After the advent of Islam, this type of literature was continued, both in poetry and in prose. From among the medieval poets one could mention Firdawsī (d. 411/1020) and Nāṣir Khusraw (d. 481/1088), while among the writers of prose such authors as Niẓām al-Mulk (d. 485/1092) or Raḍī al-Dīn Nīshāpūrī (598/1201) come to mind. Still, the most influential medieval literary work on morals is without any doubt Saʿdī's (d. 691/1291-92) Rose Garden ( Gulistān ), a mixture of poetry and tales on a variety of themes in which morals play a central role. The present work on morals by Faqīr Shīrāzī (d. 1351/1932) takes its inspiration from Saʿdī's, which it emulates in many respects. Only, its thematic arrangement was taken from Naṣīr al-Dīn Ṭūsī's (d. 672/1274) philosophical Nasirean Ethics ( Akhlāq-i Nāṣirī ), centering on the virtues of wisdom, courage, continence and their balanced compound, justice.